COMPLICATIONS OF ACUTE PANCREATITIS - Rayimov G. N; Kholmukhamedov Zh. R; Salokhiddinov N. A; Khasanov B. T; Rakhmatov D.R (Scholar Express Journals, 2023)
In the structure of patients with acute pancreatitis (AP), patients with pancreatic necrosis (PN) usually account for 15-30%, and 70-80% of them are infected with necrosis foci[1]. Postoperative mortality in GP without differentiation of its clinical forms is 23-26 %, and the proportion of purulent complications among the causes of death in patients with PN reaches 80%
Keywords: pancreatic necrosis; differential diagnosis; clinical and laboratory parameters.